Detecting Depressive Tweets by Weighted Voting Ensemble Model of Attention Based Bi LSTM and BERT with Transfer Learning - N. A., Reseena Mol; Veni, S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
A prevalent mental illness in today's world is depression. Only a small portion of the millions of people who experience depression seek adequate medical care. Prolonged depression without effective medical treatment can lead to suicide, which makes early intervention a necessity. Nowadays, people share their inner feelings through social media platforms such as Twitter, Facebook, etc., so they can be used wisely for the early detection of depression among its users. Current approaches, despite integrating machine learning techniques, frequently struggle with challenges related to accuracy and effectively capturing exact patterns present in textual data. We suggest an ensemble of standard word embedding with Bi-LSTM and advanced language model BERT with transfer learning using weighted voting to seek improved performance by resolving the current limitations and scores an accuracy of 97.4%. The novelty lies in the comprehensive utilization of advanced techniques to process and analyze social media content, contributing to early detection efforts and augmenting mental health support initiatives.